Seeding strategies of bahiagrass and pintoi peanut affect pasture establishment under weed competition. (28th February 2019) - Sanchez, Joao M. D.; Vendramini, Joao M. B.; Silveira, Maria L.; Sollenberger, Lynn E.; Dubeux, Jose C. B.; Moriel, Philipe; Sellers, Brent; Yarborough, James K.; Leite de Oliveira, Fabio C.
Abstract: Pintoi peanut ( Arachis pintoi Krapov. & W.C. Greg.) is a warm‐season perennial legume with potential for use in grass–legume mixtures in Florida; however, limited information exists about its establishment in mixtures with bahiagrass ( Paspalum notatum Flügge). The objective of this experiment was to evaluate the establishment of bahiagrass cv. "Argentine" and pintoi peanut cv. "Amarillo" as monocultures or mixture. The experiment was conducted in Ona, FL, from June to October of 2014 and 2015. Treatments were a split‐plot design of seeding strategies (bahiagrass monoculture, pintoi peanut monoculture or bahiagrass‐pintoi peanut mixtures; main plots) and two N fertilization strategies (30 or 80 kg/ha N; 30N and 80N; subplots), with four replicates. Measurements of plant density and frequency were taken every 4 weeks after seeding. Ground cover and herbage mass (HM) measurements were taken 112 days after seeding. Pintoi peanut ground cover was affected by seeding strategy × N level interaction. Ground cover was greater with 80N than 30N when pintoi was seeded in monoculture (3.6% vs 1.5% respectively) but not when it was seeded with bahiagrass (2.1%). There was no effect of seeding or N strategy on pintoi peanut proportion in HM (1.4%). Bahiagrass ground cover was not affected by seeding or N strategy (15.9%); however, its proportion in the HM was greater in 80N than 30N (12.1% vs 9.4% respectively). Mixed seeding did not negatively affect the establishment of bahiagrass and pintoi peanut and greater N fertilization levels improved some establishment parameters, with no negative effect for pintoi peanut.